The Time Dependence of Audit Firm Alumni Effects: Evidence from Audit Committees - Matthias F. Baumann; Nicole V. S. Ratzinger-Sakel (International Journal of Auditing, 2020)
This article empirically examines the time dependence of audit quality and audit fee effects resulting from the presence of audit firm alumni (AFA) on audit committees (ACs) in the German setting. Following the European Union's audit reform in 2014, the subject of this study is of particular importance, as European regulators have strengthened the position of ACs, while simultaneously restricting the presence of AFA on ACs. We find that the presence of AFA who have recently left their former employer on ACs is associated with higher audit quality, while we fail to find a significant effect on audit quality with regard to AFA who have left audit firms a longer period of time ago. In addition, the presence of AFA on ACs does not seem to affect audit fees. To the best of our knowledge, this study is the first to demonstrate time-dependent AFA effects related to ACs.
Keywords: 650; Abnormal Accruals; Audit Committee; Audit Fees; Audit Firm Alumni; Audit Quality; Cooling-off Periods; Corporate Governance; Earnings Benchmark Test; Germany; Time Dependence of Alumni Effects